"Spongy skin" as a robust strategy to deliver 4-octyl itaconate for conducting dual-regulation against in-stent restenosis. (May 2023) - Qian, Hong-Lin; Chen, Sheng-Yu; Jia, Fan; Huang, Wei-Pin; Wang, Jing; Ren, Ke-Feng; Fu, Guo-Sheng; Ji, Jian
Abstract: The valid management of inflammation and precise inhibition of smooth muscle cells (SMCs) is regarded as a promising strategy for regulating vascular responses after stent implantation, yet posing huge challenges to current coating constructions. Herein, we proposed a spongy cardiovascular stent for the protective delivery of 4-octyl itaconate (OI) based on a "spongy skin" approach, and revealed the dual-regulation effects of OI for improving vascular remolding. We first constructed a "spongy skin" onto poly-l-lactic acid (PLLA) substrates, and realized the protective loading of OI with the highest dosage of 47.9 μg/cm 2 . Then, we verified the remarkable inflammation mediation of OI, and surprisingly revealed that the OI incorporation specifically inhibited SMC proliferation and phenotype switching, which contributed to the competitive growth of endothelial cells (EC/SMC ratio ∼ 5.1). We further demonstrated that OI at a concentration of 25 μg/mL showed significant suppression of the TGF-β/Smad pathway of SMCs, leading to the promotion of contractile phenotype and reduction of extracellular matrix. In vivo evaluation indicated that the successful delivery of OI fulfilled the inflammation regulation and SMCs inhibition, therefore suppressing the in-stent restenosis. This "spongy skin" based OI eluting system may serve as a new strategy for improving vascular remolding, and provides a potential concept for the treatment of cardiovascular diseases. Graphical abstract: "Spongy skin" was constructed on PLLA stents to protectively deliver 4-octyl itaconate (OI) for improving vascular remolding. The OI-eluting stent showed a dual-regulation effect including the remarkable regulation of inflammation and suppression of SMCs proliferation, therefore realizing the inhibition of in-stent restenosis. This "spongy skin" based OI-eluting system provides a potential concept for the treatment of cardiovascular diseases. Image 1